Serum hepatitis B surface antigen correlates with tissue covalently closed circular DNA in patients with hepatitis B‐associated hepatocellular carcinoma. Issue 2 (21st July 2015) - Wang, Qin; Luan, Wei; Warren, Leslie; Fiel, M. Isabel; Blank, Sima; Kadri, Hena; Tuvin, Daniel; Hiotis, Spiros P.
Abstract : Quantitation of hepatitis B surface antigen (HBsAg) in hepatitis B‐associated hepatocellular carcinoma (HBV‐HCC) remains to be clearly defined. This study aims to determine the association of HBsAg quantity with intrahepatic HBV viral load and activity in both tumor and non‐neoplastic liver of HBV‐HCC patients. Data were obtained from 89 prospectively enrolled patients treated with primary liver resection for HBV‐HCC at a single Western institution (2008–2013). Circulating HBsAg was quantitated using ELISA. HBV DNA, covalently closed circular (cccDNA) and precore‐pregenomic RNA (preC‐pgRNA) in both tumor and non‐neoplastic liver were quantitated by real‐time PCR from fresh liver resection specimens. Circulating HBsAg was detectable in all 89 patients. HBsAg negatively correlated with age, and positively correlated with pre‐operative serum AFP and ALT levels. HBsAg correlated with HBV cccDNA copy number in tumor or non‐neoplastic liver tissue. It also correlated with preC‐pgRNA copy number in non‐neoplastic liver tissue. HBsAg did not correlate with serum HBV DNA, total intrahepatic HBV DNA, viral replicative activity or transcriptional activity. In HBV‐HCC patients, HBsAg levels correlated with cccDNA copy number in tumor or non‐neoplastic liver tissue, suggesting that a greater pool of cccDNA is associated with a higher rate of HBsAg production. J. Med. Virol. 88:244–251, 2016 . © 2015 Wiley Periodicals, Inc.